Challenging Minority Language Isolation: Translanguaging in a Trilingual School in the Basque Country. Issue 4 (4th July 2017) - Leonet, Oihana; Cenoz, Jasone; Gorter, Durk
ABSTRACT: Learning two or more languages at school is quite common all over Europe, but languages are often isolated from each other. This pedagogical practice is in contrast to the way multilingual speakers use their whole linguistic repertoire when communicating in social contexts. These multilingual solitudes are challenged when translanguaging pedagogies are used and multilingual students are allowed to use the resources in their linguistic repertoire. The specific focus of this article is to examine translanguaging as a pedagogical tool as related to a context wherein Basque is the main language of instruction, but a minority language in society. The article reports the characteristics of a pedagogical intervention based on translanguaging, which aims at developing language awareness, metalinguistic awareness, and communicative and academic competences in Basque, Spanish, and English. Our findings show that pedagogical translanguaging can be compatible with the maintenance and development of a minority language.